Uji Kinerja Sistem Elektrokoagulasi terhadap Kobalt, Nikel, dan Mangan: Performance Test of Electrocoagulation System to Cobalt, Nickel, and Manganese - Oman Sulaeman; Karina Anggraeni; Muhammad Haqqiyuddin Robbani; Taty Hernaningsih (BRIN Publishing (Penerbit BRIN), 2023)
The increasing demand for batteries for battery-based electric vehicles has caused the battery industry to grow rapidly. Batteries generally contain the heavy metals lithium, nickel, cobalt, and manganese. In solving the problem of battery’s heavy metal waste, wastewater treatment technologies is needed. One of the technologies that can be used is electrocoagulation technology. In this research, the performance test of electrocoagulation technology for the treatment of artificial wastewater containing cobalt, nickel, and manganese has been carried out. To determine the removal efficiency of the electrocoagulation system, 50 samples were collected from the processed products from each unit in the system. The results of the performance test of the electrocoagulation system showed that there was an effect of current on the pH value of artificial wastewater which increased by 11.43, 9.59, and 10.67% at currents of 10, 40, and 70 A; time affects the removal of cobalt, nickel and manganese with removal efficiencies reaching 93, 93, and 79%; and current has an effect on the removal of cobalt, nickel, and manganese in the electrocoagulation system as seen in the efficiency of removal of cobalt reaching 79, 90, and 95%; nickel removal efficiency reached 73, 85, and 97% while manganese removal efficiency was 76, 81, and 91% respectively at the same current of 10, 40, and 70 A. ABSTRAK Peningkatan kebutuhan baterai untuk kendaraan listrik yang berbasis baterai menyebabkan industri baterai berkembang pesat. Baterai umumnya mengandung logam berat lithium, nikel, kobalt, dan mangan. Dalam memecahkan masalah limbah logam berat baterai ini diperlukan teknologi pengolahan air limbah. Salah satu teknologi yang bisa digunakan adalah dengan teknologi elektrokoagulasi. Dalam penelitian ini telah dilaksanakan uji kinerja perangkat teknologi elektrokoagulasi untuk pengolahan air limbah artifisial yang mengandung kobalt, nikel, dan mangan. Untuk mengetahui efisiensi penyisihan sistem elektrokoagulasi maka dilakukan pengumpulan 50 sampel dari hasil olahan dari masing-masing unit dalam sistem tersebut. Hasil uji kinerja sistem elektrokoagulasi menunjukkan adanya pengaruh arus terhadap nilai pH air limbah artifisial dimana mengalami kenaikan sebesar 11,43, 9,59, dan 10,67% pada arus 10, 40, dan 70 A; waktu berpengaruh terhadap proses penyisihan logam kobalt, nikel, dan mangan dengan efisiensi penyisihan mencapai 93%, 93% dan 79%; dan arus berpengaruh terhadap penyisihan kobalt, nikel, dan mangan pada sistem elektrokoagulasi yang terlihat pada efisiensi penyisihan kobalt mencapai 79, 90, dan 95%; efisiensi penyisihan nikel mencapai 73, 85, dan 97% sedangkan efisiensi penyisihan mangan sebesar 76, 81,dan 91% masing-masing pada arus yang sama 10, 40, dan 70 A.